Feeding microalgae (Schizochytrium limacinum) to beef steers increases meat omega-3 content (Research, Society and Development, 2020)
New alternatives to increase the content of polyunsaturated beef fat are necessary. Feed supplements like microalgae are a strategy to enrich meat with omega 3. The aim of the study was to evaluate growth performance, fatty acid profile of meat and carcass characteristics of steers fed with microalgae in the diet. Sixteen steers (mean weight 299.6 ± 7.4 kg, seven months) were randomly assigned to two groups: the control group (CTL) and the microalgae group (ALG; daily feeding of 1.7% of dry matter as microalgae). The diet (40% corn silage and 60% concentrate) was offered twice daily for 84 days. Microalgae supplementation was associated with a 4.44-fold increase in total omega-3 fatty acids in the longissimus thoracis and lumbar muscle, reflecting a 3.6-fold reduction in the omega-6: omega-3 ratio. The concentration of 20: 5n3 and 22: 6n3 increased by 7 and 20.5 times, respectively, with the addition of microalgae. However, microalgae decreased the consumption of dry matter (P